THE ROLE OF TRUST IN MEDIATING PERCEIVED FAIRNESS AND LOYALTY IN FAMILY TAKAFUL: AN EMPIRICAL ANALYSIS - Juliana Arifin; Puspa Liza Ghazali; Norhidayah Abu Bakar; Norizan Remli; Hamizah Muhammad (Journal of Islamic, Social, Economics and Development, 2022)
Malaysia is poised to become an Asia-wide hub for Takaful, in addition to its significant contribution in Islamic finance. It is considered as a major part of the Islamic financial system, and it has continued to play an essential role in economic and social growth. Nowadays, Malaysia's Takaful industry ranks among the top three in the world. Bank Negara Malaysia report revealed that the family Takaful businesses contribute significantly to the Takaful industry's performance in Malaysia when compared to other general Takaful businesses. However, this business, particularly in family Takaful, is having difficulty keeping its current participants. It further disclosed that a wide range of family Takaful participants surrendered their certificates every year. This can be concluded that Takaful industry faces a challenge in maintain their current family Takaful participants. It is critical for the Takaful industry to focus on participants ‘retention by understanding the loyalty tendencies. Hence the main purpose of this research is to determine whether perceived fairness and trust have a significant effect to participant loyalty among those who have purchase family Takaful products. In addition, this study also examines whether trust mediates the relationship between perceived fairness and loyalty in family Takaful. The study had utilized a survey approach and took a sample of 500 respondents via four (4) Takaful operators in Malaysia, namely, Etiqa Takaful Berhad, Syarikat Takaful Malaysia Berhad, Takaful Ikhlas Sdn Bhd, and Prudential BSN Takaful Berhad. The results indicated that perceived fairness have a significant effect with participant trust, while trust has no significant effect on participant loyalty. The results also found that the trust does not mediates the relationships between perceived fairness and participant loyalty.